Analysis of Directive Speech Acts in The Film Uang Panai by Asril Sani and Halim Gani Safia - Moh Afandi; Suparni Suparni (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2025)
This study aims to describe the forms and functions of directive speech acts in the film Uang Panai and their relevance to the communicative context between characters. A descriptive qualitative method was employed in this research. The data, consisting of utterances, were collected through observation and note-taking techniques and analyzed using the theoretical framework of directive speech acts. The results reveal six categories of directive speech acts: (1) requests (14 data); (2) advice (10 data); (3) commands (9 data); (4) invitations (6 data); (5) prohibitions (4 data); and (6) criticisms (2 data). The dominance of request speech acts reflects a preference for persuasive and non-coercive communication strategies within the characters' interactions. These findings demonstrate that directive speech acts serve not only as a narrative driver for the plot but also as a representation of the cultural communication of the Bugis-Makassar community, which are deeply rooted in social values and politeness.